Chapter Overdose di storie. La narrazione senza fine dei social media - Sordi, Paolo (Moderna/Comparata, 2022)
Stories are now a distinctive and established genre in social media. From Snapchat to WhatsApp, via Facebook and Instagram, more than half a billion authors (amateurs, but not only) interact with apps by composing and consuming stories that configure new literature in which alphabetic writing coexists with the growing dominance of visual language. Centered on the narrativization of the lives of the users, invited to tell and retell themselves seamlessly, the hardware architecture and software interfaces of digital devices and media seem to generate a form of addiction to narratives, a need induced in both writing and reading. In the face of such an overdose, the question remains whether those of social media are still "stories that heal" or, rather, stories that poison.